Incretin-Based Antidiabetic Agents: A New Option for Type-2 Diabetes Mellitus (Faridpur Medical College Journal, 2011)
Type 2 Diabetes Mellitus (T2DM) is a complex disease with the co-existence of several pathophysiological abnormalities. Both microvascular and macrovascular complications are the main causes of morbidity and mortality, which develops due to endothelial dysfunction. Upregulation of reactive oxygen species, chronic inflammatory and hypercoagulable states are the pathologic basis of vascular dysfunctions in T2DM. To overcome all these abnormalities, different classes of antihyperglycaemic agents have developed. Unfortunately none is able to show satisfactory glycaemic control and to modulate vascular dysfunction. Incretin hormones are secreted from intestine during meal, which enhance insulin secretion and inhibit glucagon secretion from the pancreas. The incretin effect is severely reduced or absent in T2DM. Incretin-based new antidiabetics, both Dipeptidyl Peptidase-4 (DPP-4) inhibitors (Saxagliptin, Sitagliptin, Vildagliptin) and Glucagon Like Peptide-1 (GLP-1) analogs (Exenatide) are now being used globally. They are almost equally effective as conventional antidiabetics like Sulphonylureas (SU), Metformin (MET), Thiazolidinediones (TZD) and insulin when given as monotherapy or combined with SU, MET or TZD as second line agent. Incretin-based agents do not cause hypoglycaemia, produce weight loss in spite of weight gain and do not retain salt or water and almost no gastrointestinal (GIT) symptoms. The agents correct vascular dysfunctions and dyslipidaemia and can be given in elderly and renal impaired patients. DOI: 10.3329/fmcj.v6i1.7412 Faridpur Med. Coll. J. 2011;6(1): 51-54